Constructivism as a framework for literacy teacher education courses: the cases of six literacy teacher educators. Issue 1 (1st January 2018) - Kosnik, Clare; Menna, Lydia; Dharamshi, Pooja; Beck, Clive
Abstract: This paper presents findings from the large-scale study Literacy Teacher Educators: Their Backgrounds, Visions, and Practices that includes 28 literacy/English teacher educators (LTEs) from four countries. The participants were interviewed three times and shared their course outlines. Six pre-service LTEs who use a constructivist approach are presented. The six LTEs speak English as their mother tongue. Three aspects of constructivism are discussed: knowledge is constructed by learners; knowledge is experience based; and a strong class community is essential. They have adopted a constructivist approach because they conceptualised the teaching/learning process as a partnership. Constructivism is a flexible and fluid framework so individual LTEs can shape their work for their context and draw on their strengths; however, it is demanding because courses have to be somewhat organic in order to create space for discussion of issues as they arise.